Vocalizations, tadpole, and natural history of Crossodactylus werneri Pimenta, Cruz & Caramaschi, 2014 (Anura: Hylodidae), with comments on distribution and intraspecific variation - Vidigal, Izadora; de Carvalho, Thiago R.; Clemente-Carvalho, Rute B. G.; Giaretta, Ariovaldo A. (Zootaxa, 2018)
Crossodactylus werneri was described based on specimens collected in the 1970’s at Parque Nacional do Itatiaia, being also reported for nearby localities. We collected specimens that we assigned to C. werneri, and recorded calls of the species during fieldworks at Serra das Cabras (Campinas, state of São Paulo). In this paper, we describe for the first time the vocalizations, tadpole, coloration in life, and comment on aspects of the natural history of C. werneri. Besides, the examination of specimens in zoological collections allowed us to extend the geographic range for this species. We also make remarks on morphological/chromatic variation and provide 16S rDNA sequences for the species. Adults were found along a slow-flowing streamlet with sandy/muddy bottom within a small fragment of secondary forest. Males called between sunset and first hours of the night. Advertisement call consisted of series of pulsed notes. Call duration lasted around 3 s, emitted at the highest rate of 17 calls per minute and six notes per second. Note duration lasted around 18 ms. Notes had poorly defined pulses (irregular and/or weak amplitude modulations along the note). The dominant frequency was about 3380 Hz. Territorial call had a long, well-defined pulsed portion followed by a higher-amplitude “squeak”. The dominant frequency was around 3400 Hz. Tadpoles were essentially similar to those of other Crossodactylus species, except by not having nostril ornamentation. Our record of C. werneri in Serra das Cabras might be regarded a rediscovery of this species since C. werneri had not been recorded for more than 30 years until our first record of C. werneri in the field from 2011 and subsequent years. Our record is approximately 100 km west, and Mococa 200 km northwest, from Santo Antônio do Pinhal, the westernmost previous record for C. werneri up to date. Gene sequences (16S rRNA) give insights into the genetic divergence between C. werneri and some congeners.